2013
DOI: 10.1063/1.4840055
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of effective electron masses in highly doped nonpolar GaN

Abstract: The anisotropic effective electron masses in wurtzite GaN are determined by generalized infrared spectroscopic ellipsometry. Nonpolar (112¯0) oriented thin films allow accessing both effective masses, m⊥* and m∥*, by determining the screened plasma frequencies. A n-type doping range up to 1.7 × 1020 cm−3 is investigated. The effective mass ratio m⊥*/m∥* is obtained with highest accuracy and is found to be 1.11 independent on electron concentration up to 1.2 × 1020 cm−3. For higher electron concentrations, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…50 An isotropic electron effective mass of m e = 0.23m o was used, where m o is the free electron mass. 51 The electron-acoustic phonon deformation potential was taken as E 1 = 9.1 eV. 52 To test the model and the fitting procedure we first analyze the thermal conductivity data reported by Slack et al 7 using the steady-state heat flow method for an undoped free-standing GaN sample grown by HVPE.…”
Section: Resultsmentioning
confidence: 99%
“…50 An isotropic electron effective mass of m e = 0.23m o was used, where m o is the free electron mass. 51 The electron-acoustic phonon deformation potential was taken as E 1 = 9.1 eV. 52 To test the model and the fitting procedure we first analyze the thermal conductivity data reported by Slack et al 7 using the steady-state heat flow method for an undoped free-standing GaN sample grown by HVPE.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experimental reports have also revealed that the effective mass of degenerate wurtzite GaN can be expressed by a parabolic conduction band (α = 0) with an electron concentration as high as 1.2 × 10 20 cm 3 . 17 To improve the electron transport model of degenerate GaN with n(RT) > 1 × 10 20 cm 3 , we carefully performed temperature-dependent Hall-effect measurements. Figure 3(a) shows the temperature dependence of electron mobility for the Si-doped sample with n(RT) = 3.3 × 10 20 cm 3 .…”
Section: -mentioning
confidence: 99%
“…a) and (b) describe the variation of carrier concentration and resistivity with temperature in samples with doping levels up to the density of the Mott transition (~1-1.5×1019 cm -3 in GaN at room temperature)[28,29]. The activation energies Ea extracted from figure 5(a) decrease from 19.5 meV for the lowest doped sample A, to 12.4 meV for sample B, and 9.7 meV for sample C, in accordance with the decrease in average distance between the impurity atoms[30].…”
mentioning
confidence: 99%